THE EFFECT OF ENVIRONMENTAL, SOCIAL, GOVERNANCE ON FINANCIAL DISTRESS IN COMPANIES LISTED ON THE IDX - Mutasyah, Ainur; Hariyono, Anwar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Financial distress is a critical condition that companies experience before bankruptcy or dissolution, making its identification essential to prevent such outcomes. Specific Background: In recent years, aspects of Environmental, Social, and Governance (ESG) have gained attention as potential indicators of financial health, particularly in manufacturing companies. Knowledge Gap: However, limited research examines how ESG factors influence financial distress, especially in the context of emerging markets like Indonesia. Aims: This study investigates the impact of ESG disclosures on financial distress among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019–2022. Results: The results indicate that corporate governance disclosure has a significant negative effect on financial distress (p = 0.008), whereas environmental and social disclosures do not show a significant impact (p = 0.342 and p = 0.455, respectively). Novelty: This study highlights the distinct role of governance in mitigating financial distress, differentiating it from environmental and social disclosures, which have shown no significant effect. Implications: The findings suggest that corporate governance improvements may help companies avoid financial distress, while environmental and social factors may require further investigation for more comprehensive insights.